A Knowledge Attitude and Practice Survey Regarding Pulp Therapy Among Dental Students - NARAM, ABHISHEK; J, DR. MAHALAKSHMI; S, DR. DEEPAK (The journal of contemporary issues in business and government, 2021)
Dental pulp is an unmineralized oral tissue containing soft connective, vascular, lymphatic and nervous elements which occupies the central pulp chamber. It is the most vital part of the tooth. Vital pulp therapy is done to maintain the vitality and preserve the pulp tissue that is compromised and is indicated depending on the amount of exposure of the pulp and presence of infection. The different types of vital pulp therapy are indirect pulp capping, direct pulp capping and pulpotomy. Vital pulp therapy is also indicated for open apex to ensure proper root growth. The aim of our survey was to evaluate the knowledge attitude and practice regarding pulp therapy among dental students. A questionnaire consisting of 16 questions was distributed among dental students in saveetha dental college. Responses were collected through google forms. Data was collected and analysed using SPSS software. From the study it was concluded that there was a fair knowledge and practice regarding pulp therapy among dental students. Continuing education programs should be conducted to increase knowledge regarding pulp therapy.